Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-57798-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the early-life skin microbiota on the development of canine atopic dermatitis in a high-risk breed birth cohort

Abstract: Canine atopic dermatitis (CAD) is a prevalent inflammatory skin disease of dogs worldwide. Certain breeds such as the West Highland White Terriers (WHWT) are predisposed to suffer from CAD. Microbial dysbiosis is known to play a significant role in the pathogenesis of the disease, which is similar to its human counterpart, atopic dermatitis (AD). To date, no large cohort-study has been conducted in a predisposed dog breed to study the impact of the early-life microbiota on the development of CAD, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 63 publications
(99 reference statements)
2
24
0
Order By: Relevance
“…on the skin 46 . The most abundant genera of the early‐life skin microbiome described in our previous study 32 were not associated with the Treg cell levels in either healthy or allergic dogs except for a significant positive correlation between the relative abundance of Lachnospiraceae on the skin and the percentage of CD4 + CD25 + Foxp3 + Treg cells from allergic dogs. Genera belonging to Lachnospiraceae have been positively associated with egg allergy in children 47 .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…on the skin 46 . The most abundant genera of the early‐life skin microbiome described in our previous study 32 were not associated with the Treg cell levels in either healthy or allergic dogs except for a significant positive correlation between the relative abundance of Lachnospiraceae on the skin and the percentage of CD4 + CD25 + Foxp3 + Treg cells from allergic dogs. Genera belonging to Lachnospiraceae have been positively associated with egg allergy in children 47 .…”
Section: Discussionmentioning
confidence: 68%
“…canis ‐specific IgG levels above the cut‐off level of the test, which was determined in a previous study 21 . In our previous study in the same birth cohort, we determined Streptococcus , Lachnospiraceae family unclassified genus and Acinetobacter as the most abundant bacterial genera of the early‐life skin microbiome 32 . The Spearman’s rank correlation coefficient indicated that there was a moderate, yet significantly positive association between the relative abundance of Lachnospiraceae and the percentage of CD4 + CD25 + Foxp3 + cells in puppies that became allergic ( r = 0.568, P = 0.017) (Figure 3), and not in nonallergic puppies (Table 1).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Canine atopic dermatitis is a common inflammatory skin disorder in genetically exposed dogs associated with IgE antibodies to allergens [5,6]. Pruritus is most common clinical signs of atopic dermatitis and has the characteristics of relapse [7][8][9].…”
Section: Introductionmentioning
confidence: 99%